Transformation of Conservative Politics: A Total Politics Analysis - Şükrü Mutlu Karakoç (Siyasal: Journal of Political Sciences)
Conservative politics, which has left its mark on the last two decades of Turkish politics, has been one of the main carriers of the historical-institutional transformation in the political structure of Türkiye in that period. In the same period, conservative politics has undergone critical transformations within itself; in its internal interaction processes, it has evolved to a different point in the way that it formulates the relationship between society, politics and power. This article aims to analyze how the transformation in conservative politics took place. To this end, the authors start from the total politics analysis, which provides the opportunity to analyze Türkiye’s politics through social group behaviors. Total politics analysis argues that politics in Türkiye is shaped around in-group and inter-group power relations among the social groups at the levels of civil society, political sphere and power sphere. In this article, based on the aforementioned conceptual model, we argue that conservative politics developed a qualified relationship based on mutual interaction and autonomy between the social sphere, the political sphere and the power domains during the 2000s. We also claim that as of the 2010s, there has been a transformation in this capacity of forming a qualified relationship, which has led to a critical split within conservative politics.